Penguatan Perilaku Pro-Lingkungan Bagi Masyarakat Di Kawasan Hutan Lindung - Zairin Zairin (Universitas Prof. Dr. Hazairin, S.H, 2017)
Pro-environmental behavior is a behavior that poses a positive impact on the environment. Human behavior that does not lead to the utilization of the environment (forest) will positively degrade the environmental carrying capacity of life. The sources of forest degradation are (1) giving of forest right, (2). Forest encroachment by the population, which can be caused by The forest distance is too close to the settlement of the population, the inequality of forest tenure, the presence of brokers that offer forest land at low prices. (3). Changes in forest status so that land can be used as property or traded. This is because: forests have become the location of settlements and definitive areas, government policies that promote the interests of capital owners. (4). Forest conversion for plantation/mining, the cause: the interests of investors are more advanced, the understanding of spatial is minimal. (5). Illegal logging. The pro-environment behavior of local/indigenous peoples around protected forests can be strengthened by involving them through the provision of a larger role, resulting in a sense of ownership. Assignment of the role must be clear, what and how the role they will do. The role given to the community must be evaluated periodically so that it can be seen the accuracy of the intended target.